Political-industrial ecology: Integrative, complementary, and critical approaches. Issue 85 (October 2017) - Breetz, Hanna L.
Abstract: "Political-industrial ecology" has been proposed as an emerging subfield of nature-society geography. In mapping out the landscape of this subfield, this paper develops a typology of three approaches to connecting politics and industrial ecology: (1) Integrative research that incorporates social, political, policy, institutional, and/or spatial considerations into industrial ecology analyses ("politics in industrial ecology"); (2) Complementary research that couples findings or frameworks from industrial ecology with social and political research ("politics and industrial ecology"); and (3) Critical research that examine how values, norms, groups, political relations, or institutions shape the production, interpretation, and usage of industrial ecology knowledge ("politics of industrial ecology"). This broad framing of political-industrial ecology invites contributions from many social sciences, including political ecology, political geography, political economy, sociology, public policy, management, environmental history, and science and technology studies.